Efficacy of relacin combined with sodium hypochlorite against Enterococcus faecalis biofilms (Journal of Applied Oral Science, 2022)
Objective: Relacin is a synthetic molecule that targets RelA, an essential protein in a conserved bacterial stress response system. It was shown to inhibit bacterial growth. The aims of this study were to evaluate the antimicrobial effect of relacin combined with sodium hypochlorite (NaOCl) on Enterococcus faecalis biofilms and to evaluate the cytotoxicity of relacin. Material and Methods: 48-h E. faecalis OG1RF biofilms were treated by various concentrations of relacin in order to determine its inhibitory concentration. Then, the 48-h biofilms were treated either with 1-min NaOCl (0.01%, 0.05%) alone, or in combination of relacin. As a means of comparison, the biofilms of ΔrelA were also treated by 1-min NaOCl (0.01%, 0.05%, 0.25%). The treatment efficacy was determined by agar plate count assays. The cytotoxicity of relacin was examined on human gingival epithelial cells Ca9-22 and murine fibroblasts NIH-3T3 by a methyl thiazolyltetrazolium (MTT) assay and a lactate dehydrogenase assay. Statistical analysis was performed by one-way or two-way analysis of variance (ANOVA) with Bonferroni’s post-hoc test and an independent Student’s t-test. A significance level of p<0.05 was used. Results: Relacin inhibited the growth of OG1RF biofilms partially at 8 mM and fully at 14 mM. The relacin (14 mM) and NaOCl combined treatment resulted in significantly higher treatment efficacy than NaOCl treatment alone. At 0.05% NaOCl, the combined treatment resulted in 5.65 (±0.19) log reduction in biofilm viability. The ΔrelA biofilms were more susceptible to NaOCl treatment than the wild type biofilms at 0.25% NaOCl. Relacin at 14 mM was not toxic to host epithelial cells and fibroblasts. Conclusions: The combination of relacin with a low concentration of NaOCl was effective and not cytotoxic.